PERSEPSI WAJIB PAJAK ATAS IMPLEMENTASI SISTEM CORETAX ADMINISTRATION SYSTEM (CTAS) DAN IMPLIKASINYA TERHADAP KEPATUHAN PELAPORAN SPT TAHUNAN PADA KPP PRATAMA SURAKARTA - Desi Novitasari; Wikan Budi Utami; Suprihati (International Journal of Economics, Business and Accounting Research (IJEBAR), 2026)
This study aims to examine taxpayers’ perceptions of the implementation of the Core Tax Administration System (CTAS) and its implications for compliance with Annual Tax Return (Surat Pemberitahuan/SPT Tahunan) reporting at the Surakarta Primary Tax Office (KPP Pratama Surakarta). The study is motivated by the implementation of CTAS as a form of digital-based tax administration modernization expected to enhance service efficiency and taxpayer compliance. This research employed a qualitative approach using a descriptive method. Data were collected through interviews, observations, and documentation involving 10 informants consisting of four corporate taxpayers and six individual taxpayers who had used CTAS. Data analysis utilized the interactive model of Miles, Huberman, and Saldaña, which includes data reduction, data display, and conclusion drawing, while data credibility was tested through source and technique triangulation. The findings indicate that the implementation of CTAS is positively perceived by taxpayers as it is considered more modern, practical, and supportive of tax administration processes through integrated data features and automatic validation. Nevertheless, several technical obstacles remain, including slow server performance, login failures, and delays in one-time password (OTP) verification. Furthermore, the implementation of CTAS has positive implications for Annual Tax Return reporting compliance, as a more practical and flexible system encourages taxpayers to become more disciplined and timely in fulfilling their tax reporting obligations.